2022
DOI: 10.1186/s40729-022-00430-6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of intraoral real-time navigation versus static, CAD/CAM-manufactured pilot drilling guides in dental implant surgery: an in vitro study

Abstract: Background Nowadays, 3D planning and static for dynamic aids play an increasing role in oral rehabilitation of the masticatory apparatus with dental implants. The aim of this study is to compare the accuracy of implant placement using a 3D-printed drilling guide and an intraoral real-time dynamic navigation system. Methods A total of 60 implants were placed on 12 partially edentulous lower jaw models. 30 were placed with pilot drilling guides, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
0
5
0
1
Order By: Relevance
“…A possible explanation for this observation could be the restriction of the guide sleeve from the static template during the preparation of the borehole and implant placement, which may partially offset the resistance of the palatal bone wall of the extraction socket during immediate implant placement [ 22 ]. Robert Stünkel et al reported in their in vitro study that the dynamic CAIS system could achieve higher accuracy than the pilot drilling guide technique in posterior mandibular region of plastic models [ 23 ]. Zhaozhao Chen et al compared the deviation of the static CAIS and conventional freehand protocol in human head cadavers for immediate implant placement at the maxillary incisor site [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation for this observation could be the restriction of the guide sleeve from the static template during the preparation of the borehole and implant placement, which may partially offset the resistance of the palatal bone wall of the extraction socket during immediate implant placement [ 22 ]. Robert Stünkel et al reported in their in vitro study that the dynamic CAIS system could achieve higher accuracy than the pilot drilling guide technique in posterior mandibular region of plastic models [ 23 ]. Zhaozhao Chen et al compared the deviation of the static CAIS and conventional freehand protocol in human head cadavers for immediate implant placement at the maxillary incisor site [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…• An age of at least 18 years. • The maxillary esthetic single tooth sites (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) could not be retained due to trauma, endodontic failure, root fracture, root resorption. • Intact socket walls.…”
Section: Patient Selectionmentioning
confidence: 99%
“…An in vitro study was designed to test our hypotheses. The sample size was determined based on the results of Stünkel et al [ 25 ] and Kivovics et al [ 26 ] using G*Power 3.1 software (v.3.1.9.3, 2017, Institut für Experimentelle Psychologie, Heinrich-Heine-Universität, Düsseldorf, Germany). According to the results of these studies, an angular deviation of 4.6 ± 1.50° may be expected from a pilot-guided implant placement protocol where implant beds were finalized using straight drills, whereas an angular deviation of 3.21 ± 1.52° may be expected from pilot-guided sCAIS where step drills were used to finalize osteotomies.…”
Section: Methodsmentioning
confidence: 99%
“…При этом виде навигации выполняют остеотомию и устанавливают дентальный имплантат под наблюдением КЛКТ в реальном времени при помощи специальных рентгеноконтрастных маркеров. Динамический ХНШ позволяет менять позицию дентального имплантата интраоперационно благодаря маркерам, упомянутым выше [8][9][10][11] .…”
Section: Introductionunclassified